1441 Real-World Comparison of Curative Open, Laparoscopic and Robotic Resections for Sigmoid and Rectal Cancer - Single Center Experience. (12th October 2021) - Ansari, S. Akhter; Ahsan Javed, M; Hedayat, F; Harris, C; Sheikh, A
Abstract: Aim: There is an increase in the utilization of robotic surgery in addition to traditional open or laparoscopic approaches. The aim of this study is to compare the short-term outcomes for open, laparoscopic, and robotic surgery for rectal and sigmoid cancer. Method: One hundred and forty-seven patients (open n = 48, laparoscopic n = 49, robotic n = 50) undergoing curative resections by two surgeons, using a standardized technique, between 2013 and 2020 were included. Data analyzed included patient demographics, tumor characteristics, length of stay, post-operative outcomes, and pathologic surrogates of oncologic results, including total mesorectal excision (TME) quality, circumferential resection margin (CRM) involvement and lymph node (LN) yield. Results: Median age of population was 68 years (IQR 59-73), majority (68%) were males. Median distance from anal verge in robotic surgery group was 8 cm, compared to 15 and 14.5 cm in the open and laparoscopic groups respectively, p = 0.029, (laparoscopic vs robotic, p = 0.005 and open vs robotic, p = 0.027). Proportion of patients who received neoadjuvant radiotherapy in robotic surgery group was higher, p = 0.04. In sub-group of tumors between 3 and 7 cm from anal verge more patients in the robotic surgery group had sphincter preservation, p = 0.006. Length of stay, maximum C-reactive protein, and white blood cell rise favored minimally invasive approaches compared to open surgery. There were no differences in post-operative complications, lymph node yield or CRM positivity rate between the three groups. Conclusions: Robotic surgery approach is safe and allows sphincter preservation without compromising TME quality in rectal cancer surgery.